Roman law and maritime commerce - Candy, Peter (Peter Frank); Mataix Ferrándiz, Emilia (Edinburgh University Press, 2022)
"Bringing together specialists in ancient history, archaeology and Roman law, this book provides new perspectives on long-distance trade in the Roman world. Recent archaeological work has shown that maritime trade across the Mediterranean intensified greatly at the same time as the Roman state was extending its power overseas. This book explores aspects of this development and its relationship with changes in the legal and institutional apparatus that supported maritime commerce. It analyses the socio-legal framework within which maritime trade was conducted, and in doing so presents a new understanding of the role played by legal and social institutions in the economy of the Roman world"--Publisher's description.